2009
DOI: 10.1039/b822006a
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous generation of chemical concentration and mechanical shear stress gradients using microfluidic osmotic flow comparable to interstitial flow

Abstract: Cells are very sensitive to various microenvironmental cues, including mechanical stress and chemical gradients. Therefore, physiologically relevant models of cells should consider how cells sense and respond to microenvironmental cues. This can be accomplished by using microfluidic systems, in which fluid physics can be realized at a nanoliter scale. Here we describe a simple and versatile method to study the generation of chemical concentration and mechanical shear stress gradients in a single microfluidic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(63 citation statements)
references
References 41 publications
0
62
0
1
Order By: Relevance
“…It was reported that the cell density in the higher FBS concentration area was twice as high as that in the pure culture medium. Similarly, a microfluidic chip which can provide physiologically 145 This work realized a culture platform capable of producing chemical and mechanical stimuli similar to realistic physiological conditions. The performance of the system was evaluated by monitoring L929 mouse fibroblast cells for a continuous and long-term culture, which can be applied to the differentiation of stem cells.…”
Section: Chemical and Physical Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that the cell density in the higher FBS concentration area was twice as high as that in the pure culture medium. Similarly, a microfluidic chip which can provide physiologically 145 This work realized a culture platform capable of producing chemical and mechanical stimuli similar to realistic physiological conditions. The performance of the system was evaluated by monitoring L929 mouse fibroblast cells for a continuous and long-term culture, which can be applied to the differentiation of stem cells.…”
Section: Chemical and Physical Factorsmentioning
confidence: 99%
“…Many processing tools for HSCs are introduced and reviewed in this section including purification and separation, 145,[154][155][156][157][158] signaling analysis, [159][160][161][162][163][164] microchip electrophoresis assays, and microfluidicbased, digital, reverse transcription-polymerase chain reaction ͑RT-PCR͒ assays. [165][166][167] …”
Section: Hematopoietic Stem Cellsmentioning
confidence: 99%
“…1͒. Flow was generated by osmotic pumps and the flow rate was controlled by altering concentrations of polyethylene glycol ͑PEG͒ ͑Sigma-Aldrich, St. Louis, MO͒ in aqueous solution: [14][15][16] briefly, PDMS cubic chambers ͑inner space of 5 ϫ 5 ϫ 5 mm͒ with a window of cellulose membrane ͑5 ϫ 5 mm, used as the osmotic membrane͒ were connected to tubing and filled with de-ionized ͑DI͒ water. An osmotic pressure was generated as a result of the solute differential between the inner chamber filled with water and the outer chamber filled with PEG solution, resulting in flow.…”
Section: A Microfluidic System Designmentioning
confidence: 99%
“…Here, we utilize a previously reported osmotic pump [14][15][16] to generate the required extremely slow flows over ECs attached to the surface of a microfluidic channel rather than embedded in hydrogels and analyze their responses; modeling the internal lumen of developing blood vessel. Slow flows with extremely low shear stresses ͑10 −2 −10 −4 dyn/ cm 2 ͒, which cover a diffusiondominant flow regime which is useful for evaluating the role of the indirect mechanism, were achieved and applied to the single layered endothelial cells.…”
Section: Introductionmentioning
confidence: 99%
“…According to the results, the described device generated shear stresses spanning over at least four orders of magnitude (0.007-15.4 dyne/cm 2 ). This range of shear stresses started from an extremely low level comparable to interstitial shear stress level (Park et al 2009;Chen et al 2012;Rutkowski and Swartz 2007) to a high level which was deemed to be injurious for chondrocytes (Lee et al 2003; Healy et al 2005;Zhu et al 2010b). It also had a broader scope than previous methods and had the advantage of controlling stimulus intensity in a particular range.…”
Section: Discussionmentioning
confidence: 99%